Perbandingan Sistem Resirkulasi dan Air Mengalir Untuk Pembesaran Lobster Pasir (Panulirus Homarus): Kajian Dinamika Kualitas Air - Bambang Widyo Prastowo; Manja Meyky Bond; Betutu Senggagau (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
Aquaculture with the Recirculation Aquaculture System (RAS) is a unique engineered ecosystem that minimizes environmental disturbances by reducing the discharge of nutrient pollution through reuse of water used in fish farming. This activity was conducted at LP2IL Serang field test facility starting in June-November 2020. In this test, the RAS system used for growing of sand lobster uses the stages of purification: sedimentation, physical filtration, biological filtration, water disinfection with UV irradiation, removal of CO2, clean water reservoirs and sand lobster rearing tanks. Water quality parameters tested: a) physics: DO, pH, temperature and salinity are measured every day; b) chemistry: ammonia (TAN and UIA), nitrite, nitrate and phosphate are measured every two weeks. If from the UIA value calculation, the value is above the quality standard (> 0.05 mg / L) then added molasses (26.02% organic C) with a concentration of 64 gr / gr TAN; c) microbiology: total bacteria and Vibrio sp. counting. From the results of this study it is known that RAS can maintain stable water quality for a relatively long time. High availability of organic matter (from leftover feed, feces and addition of molasses) can promote the growth of nitrifying bacteria. The